Pemberdayaan Guru Melalui Pengembangan Media Pembelajaran Interaktif Aplikasi Articulate Storyline di SMP N 19 Semarang - Anggraini Mulwinda; Muhammad Harlanu; Agus Suryanto; Darmoyo Darmoyo (Journal on Education, 2024)
This community service activity designed to train teachers in creating interactive learning media using the Articulate Storyline application, with the hope of improving learning effectiveness. Through hands-on training and mentoring, teachers at SMPN 19 Semarang will be guided to create learning media appropriate to their respective subjects. This activity is not only beneficial for the development of teacher competence but also provides a valuable contribution to the school through the materials compiled by the service team. The implementation of this learning media is expected to be able to form a simple Learning Management System (LMS) that is useful in the learning process, both online and offline. The output targets that can be generated from this activity are: 1) Participants in this Community Service activity have knowledge and skills related to the use of Articulate learning media, 2) Participants in Community Service activities can produce learning material products that are uploaded on Articulate learning media, 3) Completion of a Journal Article published in a National Journal with ISSN, 4) Coverage of the activities of implementing community service activities in print media or electronic media.